2018
DOI: 10.1002/app.46395
|View full text |Cite
|
Sign up to set email alerts
|

Friction‐induced electroactive β polymorph of poly(vinylidene fluoride)

Abstract: Poly(vinylidene fluoride) (PVDF) has been widely used in electric devices due to electroactive b polymorph. In this article, we probe the formation of b phase under friction by spectroscopy and thermal analysis. During continuous friction, entire sliding of PVDF is identified with two regimes, i.e., running-in and steady-state. At initial running-in period, friction surfaces are dominated by plastic strain, which leads to striking formation of b phase from a polymorph (a!b). Subsequently, melting-flow domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…predominant non-polar α polymorph (≈869.7 cm −1 ), which is apparently suppressed along with adding [Li(DMF) 3 ][TFSI]. [27] Furthermore, the strong ion-dipole and dipole-dipole interactions between [Li(DMF) 3 ][TFSI] and PVDF-HFP are demonstrated through obvious IR wavenumber shifts in Figures S13 and S14 of the Supporting Information. It should be noted that there is no detectable signal of THF in IR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…predominant non-polar α polymorph (≈869.7 cm −1 ), which is apparently suppressed along with adding [Li(DMF) 3 ][TFSI]. [27] Furthermore, the strong ion-dipole and dipole-dipole interactions between [Li(DMF) 3 ][TFSI] and PVDF-HFP are demonstrated through obvious IR wavenumber shifts in Figures S13 and S14 of the Supporting Information. It should be noted that there is no detectable signal of THF in IR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The Fourier transform infrared (FTIR) absorption spectra of the final sample with a wavenumber range of 400–4000 cm –1 was obtained by using a Shimadzu IRTracer-100 spectrometer with the ATR mode. The relative content of the β-phase can be determined by the following equation where A α and A β are the absorbance at 763 and 840 cm –1 and K α and K β are the absorption coefficients of the respective bands, which values are 6.1 × 10 4 and 7.7 × 10 4 cm 2 mol –1 , respectively. ,, …”
Section: Methodsmentioning
confidence: 99%
“…The α-phase is the kinetically favorable modification and as a consequence is the crystal obtained in the customary melt crystallization. The β-phase obtained directly from the melt always requires some severe conditions, including superfast cooling, high-pressure, electric field, and mechanical treatments. Gradys et al used a thin-film chip calorimeter to investigate the PVDF crystallization with ultra-fast cooling. It was found that when the cooling rate reached 2000 K/s, the PVDF β-phase directly crystallized from the amorphous melt.…”
Section: Introductionmentioning
confidence: 99%